Electrosurgery Unit Monopolar (Cutting and Coagulation) - Ridho Armi Nabawi; Dhany Alvianto Wibaksono; Tri Bowo Indrato; Triana Rahmawati (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Electrosurgery Unit is a medical device that utilizes high frequency and voltage used to cut and dry tissue during the surgical process. The purpose of making this tool is to damage certain body tissues by heating the tissue. Heat is obtained by concentrating high frequency electricity on certain body tissues using active and passive electrodes as a medium. The Electrosurgery Unit involves the use of the CMOS 4069 IC as a frequency generator. The output frequency is set at 300 KHz then forwarded to the pulse regulating circuit and controlled with ic atmega328 then forwarded to the inverter circuit which functions to increase the voltage and output in the form of power. The module is calibrated using ESU Analyzer. This module is equipped with LOW, MEDIUM, HIGH. After the measurements are made, the more load is given higher to the tool, the higher the power released by the tool in each power selection. Then the load relationship and the power released are directly proportional. This ESU was made so that during the surgical process the body's tissue does not experience a lot of blood loss. Besides being able to use it for surgery, it can also be used to close the tissue after surgery.